Lady of Steel: Defining the Representation of Female Orthopaedic Surgeons - Sakinah Mohd Razali; Nur Dina Azman; Mohd Shaffid Mohd Sharif; Mohd Ashaari Bain; Abu Ubaidah Norazmi; Mohd Hilmi Nazarallah (UKM, 2024)
Indexed by MyCite